Allelic Variations in Aroma Gene in Cultivated Rice Varieties - Akwero, A.; Ocan, D.; Akech, W.; Lamo, J.; Ochwo-Ssemakula, M.; Rubaihayo, P. (African Crop Science Journal, 2020)
Germplasm is a valuable source of genetic diversity that supports crop improvement efforts in any breeding programme but it must first be fully characterised for economically valuable traits before it can be effectively utilised. In rice (Oryza sativa), the development of new varieties with improved aroma requires correct phenotyping and prior knowledge of the available genes and alleles governing the aroma trait in the gene pool. Correct phenotyping and genotyping can be achieved using sensory methods and functional markers associated with polymorphisms that define the aroma genes. The objective of this study was to evaluate the aroma status of rice accessions and to assess for the various alleles of badh2 gene using functional markers. A total of 56 rice accessions were evaluated at National Crops Resources Research Institute (NaCRRI) in Uganda for their aroma using sensory methods and a molecular marker to differentiate between aromatic and non- aromatic accessions. The aromatic accessions were then evaluated for variations within the betaine aldehyde dehydrogenase2 (badh2) gene responsible for aroma in rice using functional markers. Sensory evaluation of aroma identified 23 accessions to be aromatic; while 33 were non-aromatic. Molecular results identified 20 accessions as aromatic; while 36 accessions were non-aromatic. Functional marker analysis indicated the presence of badh2-E7 allele in 20 aromatic accessions within this collection that could be employed in the breeding programme for the rice aromatic trait.
Keywords: Badh2 alleles; Functional markers; Oryza sativa